Influence of European Beech (Fagales: Fagaceae) Rot Hole Habitat Characteristics on Invertebrate Community Structure and Diversity. Issue 5 (23rd September 2021) - Cuff, Jordan P; Windsor, Fredric M; Gilmartin, Emma C; Boddy, Lynne; Jones, T Hefin
Abstract: Hollows of veteran trees (i.e., rot holes) provide habitat for many rare and threatened saproxylic invertebrates. Rot holes are highly heterogeneous, particularly in terms of substrate and microclimate conditions. There is, however, a dearth of information regarding the differences in biological communities inhabiting rot holes with different environmental conditions. Invertebrates were sampled from European beech ( Fagus sylvatica ) rot holes in Windsor, Savernake, and Epping Forests (United Kingdom). For each rot hole, physical and environmental conditions were measured, including tree diameter, rot hole dimensions, rot hole height, substrate density, water content, and water potential. These parameters were used to assess the influence of environmental conditions and habitat characteristics on invertebrate communities. Rot hole invertebrate communities were extremely diverse, containing both woodland generalist and saproxylic specialist taxa. Large variation in community structure was observed between rot holes and across woodlands; all sites supported threatened and endangered taxa. Environmental conditions in rot holes were highly variable within and between woodland sites, and communities were predominantly structured by these environmental conditions. In particular, turnover between invertebrate communities was linked to high β-diversity. The linked heterogeneity of environmental conditions and invertebrate communities in rot holes suggests that management of deadwood habitats in woodlands should strive to generate environmental heterogeneity to promote invertebrate diversity. Additional research is required to define how management and conservation activities can further promote enhanced biodiversity across rot holes.